Delivering Agile Marketing Projects: A View from Practice - Blair, Garry; Betts, Peter; Conway, Tony; Hyde, Margaret; Pagano, Rosane (Apex Journal of Business and Management, 2024)
Successful marketing projects are vital to most organisations to ensure their survival. The paper advocates an 'agile approach' in creating effective marketing initiatives. It underscores the necessity of clearly defined objectives and internal efficiency, addressing power issues for optimal resource allocation. Brand definition, understanding the customer base through profiling, and implementing a differentiated, segmented approach are crucial aspects. The paper recommends data gathering for analysis and leveraging technology to support these projects, all encapsulated within the 'agile approach.' The research methodology involved a survey of literature, complemented by a semi-structured group interview with experienced UK-based marketing professionals. Inductive analysis was applied to the gathered data, extracting principal themes. The outcome of this research proposes a framework for delivering 'Agile marketing projects' based on a project management 'learning' model. This structured approach contributes valuable insights for organizations seeking success in their marketing endeavors.